1996
DOI: 10.1002/jlb.59.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Rapid killing of human neutrophils by the potent activator phorbol 12-myristate 13-acetate (PMA) accompanied by changes different from typical apoptosis or necrosis

Abstract: To elucidate the relationship between activation of neutrophils and their subsequent death, the effect of phorbol 12-myristate 13-acetate (PMA), a potent activator of neutrophils, was examined. PMA-treated neutrophils showed morphological changes quite different from those of typical apoptosis or necrosis. After fusion of the lobate nucleus, nuclear contents of chromatin uniformly decreased in compactness and soon after the nuclear envelope was broken. Even at this stage, cytoplasmic organelles did not undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
244
1
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(258 citation statements)
references
References 26 publications
6
244
1
7
Order By: Relevance
“…In fact, we observed that superoxide production was completely blocked by staurosporine in Me 2 SO-differentiated HL-60 cells stimulated by PMA. These findings concur with the previous observation that staurosporine prevents PMA-induced cytotoxicity in neutrophils (34). Thus, staurosporine is able to prevent NADPH oxidase-dependent oxidative stress and subsequent oxidantinduced apoptosis in Me 2 SO-differentiated HL-60 cells.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, we observed that superoxide production was completely blocked by staurosporine in Me 2 SO-differentiated HL-60 cells stimulated by PMA. These findings concur with the previous observation that staurosporine prevents PMA-induced cytotoxicity in neutrophils (34). Thus, staurosporine is able to prevent NADPH oxidase-dependent oxidative stress and subsequent oxidantinduced apoptosis in Me 2 SO-differentiated HL-60 cells.…”
Section: Discussionsupporting
confidence: 93%
“…In those cases, a decreased TOT(inside) value may arise from TB quenching because the neutrophils' cell surface might become permeable as a consequence of uncontrolled cell death letting vital dyes, such as TB, through the membrane. There is evidence that uncontrolled cell death can be a consequence of increased intracellular production of oxygen radicals induced by phorbol 12-myristate 13-acetate or zymosan (37). In addition, extracellular oxygen radicals, whose concentration can increase quite high, may be able to damage the cell membrane.…”
Section: Calculated Phagocytotic Parametersmentioning
confidence: 99%
“…PMA was used as neutrophil stimulator because its effect is closely analogous to that obtained during the phagocytic process with an activation of protein kinase C, which results in NADPH oxidase activation, with subsequent production of reactive species (Takei et al, 1996). The luminol probe reacts unspecifically with ROS and RNS (O , and therefore may be considered a useful tool to evaluate the Table 1.…”
Section: Resultsmentioning
confidence: 99%